Comparison of Production Costs in the Financial Statements PT Japfa Comfeed Indonesia Tbk With PT Charoen Pokphand Indonesia Tbk Using Number Index - Insan Kamil; Widiya Astuti Alam Sur; Tekad Budiantoro (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
This study used a relatively simple price and an unweighted aggregate price index number used to calculate the level of production cost annually in the form of a percent. The use of this index number is to compare the current year period divided by the based year and multiplied by 100%. The purpose of this study is to analyze the comparison of production costs from animal feed companies in Indonesia, namely PT Japfa Comfeed Indonesia. Tbk and PT Charoen Pokphand Indonesia Tbk in 2014-2018 with 2014 as the base year. Based on the calculation of production costs using the index number method at PT Japfa Comfeed Indonesia Tbk and PT Charoen Pokphand Indonesia Tbk there is an increase and decrease in production costs. PT Charoen Pokphand Indonesia Tbk has better production costs than PT Japfa Comfeed Indonesia Tbk because the profits of PT Charoen Pokphand Indonesia Tbk company have increased more than PT Japfa Comfeed Indonesia Tbk every year.